Analisis Implementasi Pembelajaran Tematik Berorientasi Multiple Intelegences di Kelas Rendah SD/MI - Rendy Nugraha Frasandy; Sonya Yuliantika (Universitas Islam Negeri Imam Bonjol Padang, 2023)
This research is motivated by the lack of understanding of educators on the intelligence of students. Referring to these problems, thematic learning based on multiple intelligences can develop various intelligences of students in learning. The role of educators is needed in implementing multiple intelligences-based thematic learning for elementary school students. Educators must realize the importance of learning by not only emphasizing one intelligence but also exploring the intelligences possessed by students. The purpose of the study was to analyze the extent to which elementary/MI low grade educators were able to apply thematic learning oriented to multiple intelligences. This research is library research, that is, using library resources to obtain research data on Research and development (R&D) development. The data sources used in this research are books, journals and internet sites related to the chosen topic. Data collection techniques in this study are descriptive and analysis. The data analysis technique in this literature research is analysis at the time of data collection, this is intended to better capture the essence or core of the focus of the research to be carried out through the sources collected and contained in the verbal linguistic formulation, this process is carried out aspect by aspect, in accordance with research map. The results of this study indicate that the application of thematic learning in elementary/MI low grades strongly supports the development of multiple intelligences (multiple intelligences) of students. This is corroborated by the data that the 9 intelligences possessed by students are applied to the theme books for grade 2 SD/MI Theme 1 “live in harmony” Subtheme 1 “live in harmony at home”.